Pengaruh Pemberian Compression Garment dan Abdominal Lymphatic Drainage Massage Dengan Teknik Effleurage terhadap Lymphedema pada Pasien Post Operasi Liposuction Abdomen di Rumah Sakit Bimc Nusa Dua - Luh Putu Citra Dewi Jayanti; Dewa Ayu Alit Darmayani; Dian Febiola Christian; Ni Kadek Desi Antari (Universitas Malahayati, 2024)
ABSTRACT Liposuction is a procedure to remove subcutaneous fat. One of the side effects is lymphedema, which, if left untreated, can lead to serious complications. BIMC Nusa Dua Hospital applies compression garment and lymphatic drainage to reduce lymphedema after abdominal liposuction. This study aims to evaluate the effects of both therapies. The aim of this study was to determine the effect of giving compression garments and abdominal lymphatic drainage using the effleurage technique on lymphedema in post-abdominal liposuction surgery patients at BIMC Nusa Dua Hospital in 2024. Methods This research used a quasi-experimental method with 32 subjects divided into control and control groups. treatment. Abdominal circumference measurements were taken before and after treatment. Data analysis used the Independent T-test. The results show that there is an effect of giving compression garments and lymphatic drainage on lymphedema in post-abdominal liposuction patients with the results of the Independent T-test showing a p value 0.05 at the three waist circumference measurement points. Conclusion: The combination therapy of compression garment and abdominal lymphatic drainage is effective in reducing post-liposuction lymphedema. These findings can guide further therapy for liposuction patients. Keywords:Compression Garment, Abdominal Lymphatic Drainage, Lymphedema, Liposuction ABSTRAK Liposuction adalah prosedur untuk menghilangkan lemak subkutan. Salah satu efek sampingnya adalah limfedema, yang jika tidak diobati, bisa mengakibatkan komplikasi serius. RS BIMC Nusa Dua menerapkan compression garment dan lymphatic drainage untuk mengurangi limfedema pasca liposuction abdomen. Studi ini bertujuan untuk mengevaluasi efek kedua terapi tersebut. Tujuan penelitian ini adalah untuk Mengetahui pengaruh pemberian compression garment dan abdominal lymphatic drainage dengan teknik effleurage terhadap lymphedema pada pasien post operasi liposuction abdomen di Rumah Sakit BIMC Nusa Dua tahun 2024. Metode Penelitian ini menggunakan metode quasi-eksperimental dengan 32 subjek dibagi menjadi kelompok kontrol dan perlakuan. Pengukuran lingkar perut dilakukan sebelum dan setelah perlakuan. Analisis data menggunakan uji Independent T-test. Hasil menunjukkan Ada pengaruh pemberian compression garment dan lymphatic drainage terhadap limfedema pada pasien post liposuction abdomen dengan hasil uji Independent T-test menunjukkan nilai p value 0.05 pada ketiga titik pengukuran lingkar pinggang. Kesimpulan Terapi kombinasi compression garment dan abdominal lymphatic drainage efektif dalam mengurangi limfedema pasca liposuction. Temuan ini dapat menjadi panduan terapi lanjutan bagi pasien liposuction. Kata Kunci: Compression Garment, Abdominal Lymphatic Drainage, Limfedema, Liposuction